Implementasi Teknologi Augmented Reality Pada Perancangan Media Ajar Interaktif Iqra' Jilid 1 - Kalimusodho, Ibnu; Pradhana, Faisal Reza; Harmini, Triana (Innovative: Journal Of Social Science Research, 2025)
In today's ever-evolving digital era, product and service marketing has become increasingly complex, demanding higher levels of innovation. One of the latest trends in marketing is the use of Augmented Reality (AR), which holds great potential to transform the way consumers interact with products and services. AR technology enables users to experience a blend of the physical and virtual worlds, creating more engaging and interactive experiences. As a result, teaching aids based on Augmented Reality (AR) are needed as interactive learning media. This study aims to develop and implement AR-based teaching media within a marker-based Android application to visualise 3D elements and interactive virtual objects. The media design process follows the stages of the System Development Life Cycle (SDLC), commonly known as the waterfall method. The result of this research is an application called "AR-Iqro," which features multimedia visualisations in both two and three dimensions. The application was tested through four steps, including feature testing using the black-box method, achieving a 100% success rate. Additionally, compatibility tests were conducted to ensure the application's performance across various Android devices. Further evaluations involved distributing questionnaires to teachers and educators, yielding an average satisfaction rate of 9%. In conclusion, the AR-based teaching media application, using marker-based technology, is deemed "highly suitable" as an effective tool for enhancing teaching and learning activities (TLA).